Комплексний аналіз ризику банкрутства корпорацій в умовах невизначеності. Частина 2 - Zgurovsky, M. Z.; Zaychenko, Yu. P. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2012)
Different methods of enterprise bankruptcy risk analysis with application of fuzzy neural networks with the algorithms of finding Mamdani and Zukamoto are proposed. Experimental research of a clear method of Altman, fuzzy multi-method of Nedosekin and FNN in problems of analysis of risk of bankruptcy, which are considered on the example of the enterprises of Ukraine, are carried out, their efficiency is estimated and the most adequate method for Ukrainian economy was determined.